A QR Code-Based Real-Time Auditing System for Safe Online Data Storage - S. Suman Rajest; R. Regin; Shynu T; Steffi. R (International Journal on Human-Computing Studies, 2024)
Up until now, auditing systems have only had a web module; these modules are complicated and not user-friendly. Protecting sensitive data stored in the cloud requires the time-consuming and laborious procedure of encrypting all of the files. To verify a user's identification in the current system, the client must input biometric data. Next, in order to safeguard the user's identity and privacy, a signature key will be validated. One major problem with biometric data is that there are a lot of circumstances that might cause it to vary, so it can't always be matched precisely. An auditing and data storage app built for the cloud is the focus of this paper. The reference ID that the client creates is used to remotely store the financial audit data in the cloud. Using a QR code scanner, this reference ID that was generated for the client is immediately transformed into a QR code. You can access the required documents by downloading them and then opening them in a dedicated app. In the event that the client's internal storage becomes corrupted or lost, this file can be restored from the cloud.